Comparative safety and tolerability of duloxetine vs. pregabalin vs. duloxetine plus gabapentin in patients with diabetic peripheral neuropathic pain. Issue 9 (18th May 2014) - Irving, G.; Tanenberg, R. J.; Raskin, J.; Risser, R. C.; Malcolm, S.
Summary Objective The safety and tolerability of three treatments for diabetic peripheral neuropathic pain (DPNP) were compared. Methods A 12‐week, randomized, open‐label study confirming the non‐inferiority of duloxetine (N = 138) vs. pregabalin (N = 134) and the combination of duloxetine plus gabapentin (N = 135) as the primary outcome was previously published. Patients had an inadequate pain response to a stable dose of gabapentin (≥ 900 mg/day) for ≥ 5 weeks prior to study enrolment. Data from that study were assessed in this current analysis for a detailed report of safety and tolerability. Results Completion rates did not differ significantly between the groups. Discontinuation because of adverse events was significantly greater in the duloxetine (19.6%) vs. pregabalin group (10.4%; p = 0.04); no differences emerged between the duloxetine vs. duloxetine plus gabapentin (13.3%) groups (p = 0.19) or pregabalin vs. duloxetine plus gabapentin groups (p = 0.57). Adverse event rates varied: nausea, insomnia, hyperhidrosis and decreased appetite were reported significantly more often in patients treated with duloxetine vs. patients treated with pregabalin (each p ≤ 0.01); insomnia significantly more in patients treated with duloxetine vs. duloxetine plus gabapentin (p = 0.01); peripheral oedema significantly more in patients treated with pregabalin vs. duloxetine and duloxetine plus gabapentin (p ≤ 0.001 each) and nausea, hyperhidrosis, decreased appetite and vomiting significantly more in patients treated with duloxetine plus gabapentin vs. pregabalin (each p ≤ 0.05). At end‐point, weight change differed significantly among treatment groups: patients in the pregabalin group on average gained weight (1.0 ± 0.04 kg); while, patients in the duloxetine and duloxetine plus gabapentin groups on average lost weight (−2.39 ± 0.04 and −1.06 ± 0.04 kg, respectively) (pregabalin vs. duloxetine, p ≤ 0.001; pregabalin vs. duloxetine plus gabapentin, p ≤ 0.001; duloxetine vs. duloxetine plus gabapentin, p = 0.01). Conclusion Duloxetine, pregabalin and duloxetine plus gabapentin were generally safe and tolerable for the treatment of DPNP.